STRATEGI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN TEMANGGUNG DALAM UPAYA PENINGKATAN KEPEMILIKAN AKTA KELAHIRAN - Siti Rozana; Achmad Taufik (Journal of Politic and Government Studies, 2018)
Birth Certificate is an official document issued by the Department of Population and Civil Registration. Birth Certificate is very important because in important events such as birth, marriage, divorce etc. will bring the legal consequences for peoples. Due to the importance of these birth certificates, the Department of Population and Civil Registration of Temanggung Regency made efforts to increase the Birth Certificate Ownership Strategy so that in 2015 the Population and Civil Registration Agency of Temanggung Regency gets the 2nd national level award on the fulfillment of Birth Certificate. Therefore, this research is aimed to find out how the strategy of increasing Birth Certificate Ownership conducted by the Department of Population and Civil Registry of Temanggung Regency. This research uses descriptive qualitative research method with documentation and interview as data collection technique. The targets of this research are the government, especially the Department of Population and Civil Registry of Temanggung Regency. The strategy of this research is the form of steps or ways that the government does in the long run to achieve the goal. Based on the results of the research as a whole the problems faced by the Department of Population and Civil Registration of Temanggung Regency related to the strategy of increasing ownership of Birth Certificate is the lack of human resources and the lack of participation from the village apparatus to socialize to the community. This research recommends that all government elements, both the Department of Population and Civil Registration and the Village Government, work together to realize the ownership of the Birth Certificate as a whole in Temanggung Regency. The Key : Birth Certificate, Strategy, Human resources, Coorporation